Promoting student participation skills through student organizations - Hidayah, Yayuk; Su Fen, Cheong; Suryaningsih, Anis; Mazid, Sukron (Universitas Negeri Yogyakarta, 2022)
A student organization is a step used to improve students' basic norms, roles and learning functions in accordance with the Indonesian Ministry of Education and Culture number 155/1998. Conversely, Law number 12 of the 2012 government regulation amended in 2014 on the Implementation and management of Higher Education did not provide more details on student organizations. Student organizations under the auspices of the Ministry of Religion of the Republic of Indonesia tend to be independent in their management with the establishment of Decree (S.K.) by the General Director of Islamic Education number 4961 in 2016. Therefore, this study aims to describe, analyze, and explore students' participation in fostering their organizations through a series of working programs. These programs were predicted to be a medium for students to participate in their communities after they had graduated from college. This is qualitative research with semi-structured interviews, observation, and literature studies as instruments to collect data from 24 informants from eight different campuses in the Special Region of Yogyakarta (D.I. Yogyakarta). The result shows that student participation in organizations includes cadre formation, leadership skills, and educational awareness. Implementing a working program is an operational concern for members on campus; therefore, it is a medium for a country to gain knowledge, prepare for the future, and self-actualize its citizens from the perspective of competency.